Swarm navigation of cyborg-insects in unknown obstructed soft terrain - Yang Bai; Phuoc Thanh Tran Ngoc; Huu Duoc Nguyen; Duc Long Le; Quang Huy Ha; Kazuki Kai; Yu Xiang See To; Yaosheng Deng; Jie Song; Naoki Wakamiya; Hirotaka Sato; Masaki Ogura (Nature Communications)
Abstract Cyborg insects refer to hybrid robots that integrate living insects with miniature electronic controllers to enable robotic-like programmable control. These creatures exhibit advantages over conventional robots in adaption to complex terrain and sustained energy efficiency. Nevertheless, there is a lack of literature on the control of multi-cyborg systems. This research gap is due to the difficulty in coordinating the movements of a cyborg system under the presence of insects’ inherent individual variability in their reactions to control input. Regarding this issue, we propose a swarm navigation algorithm and verify it under experiments. This research advances swarm robotics by integrating biological organisms with control theory to develop intelligent autonomous systems for real-world applications.